Reducing vulnerability to climate change among millet and sorghum farmers in Ghana: interrogating the contribution of climate-smart agriculture in northwestern Ghana - Yiridomoh, Gordon Yenglier; Bonye, Samuel Ziem; Derbile, Emmanuel K. (Frontiers in Sustainable Food Systems, 2024)
Reducing vulnerability of smallholder farmers to climate change is a global issue. One approach viewed as important in reducing farmers’ vulnerability to climate change is Climate-Smart Agriculture (CSA). CSA is often seen as an approach to redefine, reposition and sustainably manage agriculture. Given the importance of CSA practices in sustaining the food needs of many farm households in sub-Saharan Africa and Ghana, this study investigates CSA practices that were introduced to farmers by Center for Indigenous Knowledge and Development (CIKOD), interrogates the contributions of CSA to reducing farmers vulnerability to climate change and established the relationship between CSA and climate change adaptation. The study employed a mixed method approach, using 146 smallholder millet and sorghum farmers. Questionnaire and interviews were used to generate primary data for analysis. Descriptive statistics, involving Chi-square test and relative importance index were used to analyze the questionnaire while thematic analytical approach was used to analyze the interviews. The results of the study revealed that CSA practices such as crop rotation, weed control, contour farming, and land rotation are deployed by smallholder farmers to respond to drought, dry spell and flood in the Municipality. Asset holding capacity, credit, access to climate information, and extension services were found to be key determinants of farmers’ adoption of CSA practices. The study recommends the need for the Ministry of Food and Agriculture to provide some technical support to smallholder farmers to successfully adopt these practices for sustainable farming. Again, the study recommends the need for non-governmental organizations and development partners, which over the years have shown interest in promoting CSA practices among farmers, to continuous to support and promote the adoption of CSA by farmers.